Невозвратный билет: [рассказы] / Маша Трауб - Трауб Маша (Эксмо, 2022)
Экземпляры: (20230404) / Инвентарный номер: 64547 / Цена: 391.00 / Сис.шифр: Р2 / Авт.знак: Т 65 / ГРНТИ: 17.82.32 / ББК: 84(2Рос=Рус)6